Interpretation of Culture Heritage in Latvian Ethnographic Open Air Museum - Burceva, Rita (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2013)
The aim of the article is to study the peculiarities of interpretation of the cultural heritage, using the case of the Ethnographic Open Air Museum of Latvia as a basis for research. The methods used in the research are the review of documents and theoretical literature, observation, and case study. Latvian farmstead with its architecture and design is included in the Latvian Cultural Canon; therefore thorough studies of such units would promote the development of the cultural education potential in the society. There are some authentic examples of the wooden building ensembles from Vidzeme, Zemgale, Latgale and Kurzeme in the territory of the Ethnographic Open-Air Museum of Latvia. The Ethnographic Open-Air Museum of Latvia corresponds with the criteria of an Open-air museum: it comprises the exhibition of several buildings, as well as reconstructs and reflects the content of the daily lifestyle of previous generations. There are both collective and individual services available here, where visitors can organize their visit there depending on their interests. Possession of previous information of what is being exhibited in the museum, and the depth of preliminary knowledge of the museum’s visitors can have a significant effect on the content of the communication process in the museum. If the visitors represent a group of specialists of one sector or another, then according to the level of competence of the public some specific terminology is used in communication. Otherwise the interests of the visiting persons are not completely satisfied. Whereas, in the event of a lack of knowledge the museum personnel should select the appropriate lexicon and volume of information, which doesn’t exhaust their visitors but promotes thorough studies of the cultural heritage. Under these circumstances the possibilities for interpretation of the museum collections are of significant importance, because a visitor needs external assistance in order to absorb in the content, shades of the exhibition, in order to get to the bottom of it and to accept the newly discovered values. Museum visitors, who haven’t applied for a guided tour, get their views independently, observing the museum articles, comparing the seen with their previous experience or seeking its confirmation / generalization, getting involved in the verbal communication with the museum employees as much as it is possible. All of it together creates an emotional background of the ongoing situation. An empirical observation is organized analogously; a researcher gets some impression, information and knowledge, facts, putting them down in the minutes, and supplementing them with some notes and comments right after the observation is completed regarding the problems of interpretation of the cultural heritage set in the objective of the research. Interpretation of the cultural heritage is an individual action because it depends on the preliminary knowledge, interests of museum visitors, the aims of their visits, the specifics of exhibitions, style of communication in the museum. The peculiarities of interpretation of the communication and cultural heritage of the Ethnographic Open-Air Museum of Latvia are associated both with positive (the availability of preliminary information on the museum and exposition, varied infrastructure and amenities for visitors, the possibility of communication with the museum employees in its territory, the horizontal direction of communication, a possibility to interact with the museum objects, etc.), and negative aspects (unavailability of printed materials, a lack of descriptions under the museum exhibits, the communication limited by time, etc.).